The Roles of Price on Rebates and Implication to Customer Product Choice: Study on One of The Health Drink Brands in Bandung - Anton Tirta Komara (Jurnal Ekonomi, Bisnis & Entrepreneurship, 2023)
A comprehensive comprehension of the various factors influencing consumer purchasing decisions is crucial for success in the highly competitive business environment. The findings of this study examine the significant role that price and discounts (rebates) play in consumer decision-making. The study's findings emphasize the considerable influence of price on consumers' decision-making regarding product selection. Consumers tend to seek out more affordable alternative options when there is an increase in the price of a product. Nevertheless, in the event of a compelling discount, consumers tend to transition and opt for the alternative product swiftly. Furthermore, this study demonstrates that individuals' financial capabilities impact their decision-making process when it comes to selecting products. Consumers exhibiting elevated financial capacities are inclined to prioritize personal preferences when making product selections rather than solely focusing on price considerations. This observation indicates that individuals with greater purchasing power are afforded a more comprehensive range of options when selecting products. However, it is imperative to exercise caution as price similarity assumes a significant role in consumers' decision-making process. Consumers tend to favor products that align with the price they have paid. Nevertheless, the analysis findings suggest the necessity for additional research to gain a more comprehensive understanding of this correlation. In addition, the discounts provided by companies also impact consumers' perceptions of prices and their financial capacities. Discounts can significantly impact consumers' perceptions of product prices, enabling them to select items previously perceived as unaffordable. This study offers significant insights into the impact of price, discounts, and financial capabilities on consumer purchasing preferences. The findings of this study establish a robust basis for corporations to develop enhanced marketing strategies, considering the significant influence these variables exert on consumer decision-making processes. Enhanced comprehension of consumer behavior enables companies to attain heightened levels of success within a fiercely competitive market.